Contributions individuelles d’étudiants en formation initiale à l’enseignement des sciences à la construction d’un discours autour d’un thème intégrateur - Christine Hamel; Sylvie Barma (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
Our study shows how two professors created a zone of convergence between two compulsory courses in the Bachelor of Secondary Education program in Quebec. In order to promote a process of professional development rooted in a socioconstructivist perspective, the students worked collaboratively to develop laboratory learning situations that incorporated the concepts studied in their classroom management course and their science education course. We present the pedagogical approach implemented in the two courses as well as the collaborative discourse co-constructed by the students during the Fall 2011 semester. Our results demonstrate the relevance of such an approach for supporting students' ability to engage in a well-argued theoretical discourse on creating laboratory situations and the possible links with the management of classroom interactions.